استثمار مقاصد الشريعة في حفظ الأمن والنظام العام - Meriem Attia Bouziane (Al-Zahra : Journal for Islamic and Arabic Studies, 2023)
The research highlights the preservation of the general system as a legitimate intent, although it does not appear among the necessary overall purpose grades. The researcher also tried to demonstrate the ways in which the rank of security is determined between being a destination and being a means and demonstrating the difference between them in the impact and the judgment they entailed. Based on the extrapolation that showed that the ultimate goal of the messenger's dispatch is to preserve the order of the group, which God mused about the need to meet in order to meet the needs, achieve interests and drive the corrupt. Nor did it lose sight of the fundamentalists' efforts and attempts to legitimately root for public order